Climate Resilient Road Assets in Albania - Xiong, Jing; Espinet Alegre, Xavier (World Bank, Washington, DC, 2019)
This report consolidates the findings and recommendations from studies on climate resilient road assets in Albania, financed through a grant provided by the Global facility for disaster reduction and recovery (GFDRR). The objective of the work is to assist the Albanian authorities in the prioritization of current and future climate, and seismic resilient investments in the road sector. The work has used climate and seismic vulnerability assessments, and proposed mitigation measures to improve climate and seismic resilience of the Albanian road network. The report finds that the investment in resilience and mitigation measures on the Albanian national road network is cost effective and is much less than the estimated annualised cost of the damage and loss that would accrue if mitigation measures are not put in place and maintained.